Effect of chemical admixtures on borogypsum containing cement mortar - Kunt, Kubra; Dur, Fatma; Yildirim, Meral; Derun, Emek Moroydor (IOS PRESS, 2017)
In this study, the influences of air-entraining, set accelerating and superplasticizer admixtures on the properties of borogypsum containing cement mortars were investigated. According to results, by using 3% borogypsum and water/binder ratio of 0.45, the compressive and flexural strength values were increased up to 196.38%. The usage of various ratios of air-entraining and set accelerating admixtures showed reverse effects on the compressive and flexural strength. However, 0.4% superplasticizer containing mortars had 65.39MPa compressive strength and 9.08MPa flexural strength which were 33.12% and 26.82% higher than the reference. Durability test results showed addition 3% borogypsum provided endurance to sulfate attacks up to 30 days.
Keywords: Borogypsum; chemical admixtures; durability; mortar; AIR ENTRAINING AGENT; PORTLAND-CEMENT; FLY-ASH; CONCRETE; COLEMANITE; BORON; WASTE; SUPERPLASTICIZERS; HYDRATION; Chemistry